2008
DOI: 10.1007/s10705-008-9206-y
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Brachiaria humidicola pastures in the Atlantic forest region of Brazil as affected by stocking rate and the presence of a forage legume

Abstract: Excessive intensification of dairy and beef cattle production systems in the industrialised countries has led to serious problems of pollution of water resources and the atmosphere. In order to develop an appropriate alternative, a few studies have been made by various research teams in Brazil, using low fertiliser inputs and modest animal stocking rates. The objective of this present study was to evaluate the effect of different stocking rates of beef cattle, and the introduction of a forage legume (Desmodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
12
1
6
Order By: Relevance
“…The effect of grass v. legume on ADG could not be assessed for the full database because it was only assessed in two papers (Romero and Siebert, 1980;Pereira et al, 2009), showing that ADG was not significantly affected by the type of forage (average of 3.49 ± 1.51 for a grass-legume mix v. 2.03 ± 1.77 g/kg BW for grass alone; P < 0.005).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of grass v. legume on ADG could not be assessed for the full database because it was only assessed in two papers (Romero and Siebert, 1980;Pereira et al, 2009), showing that ADG was not significantly affected by the type of forage (average of 3.49 ± 1.51 for a grass-legume mix v. 2.03 ± 1.77 g/kg BW for grass alone; P < 0.005).…”
Section: Resultsmentioning
confidence: 99%
“…No entanto, com a cultivar Comum, o CMS foi maior no período das águas. Pereira et al (2009) também observaram maior CMS durante o período das águas para essa cultivar. Os baixos CMS observados nas duas espécies, e nos dois períodos, podem ser explicados pelos baixos teores de PB nas forrageiras (Tabela 2).…”
Section: Resultsunclassified
“…Teores de PB na dieta abaixo de 6% reduzem a atividade dos microrganismos do rúmen, o que resulta em decréscimo nas taxas de digestão e de passagem do alimento, bem como no consumo voluntário pelos animais Minson (1990). Ressalta-se que os valores CMS obtidos para as duas cultivares, durante o período das águas, foi bem inferior ao observado por Pereira et al (2009) para com a cultivar Comum.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The composite index is an average of all three individual services. Sources: Raich et al 1991, Fearnside and Barbosa 1998, Marsden et al 2001, Freixo et al 2002, Guo and Gifford 2004, Cockle et al 2005, Laclau et al 2008, Uezu et al 2008, Pereira et al 2009, Fialho and Zinn 2012 Marsden et al 2001| †Obtained by dividing the number of forest species observed in the "L1" matrix by the 43 species observed in control plots and large patches ‡Obtained by dividing the number of forest species observed in the agroforest patches by the number of species observed in control plots and large patches §2.9 species/ha |Obtained by dividing the number of forest species in eucalyptus plantations by the number of species in Atlantic Forest fragments…”
Section: Ecosystem Servicesmentioning
confidence: 99%